(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This article discusses the application of the Team Assisted Individualisation (TAI) cooperative learning model in an effort to increase students’ interest in learning Fiqh. This study aims to describe the process of implementing the TAI model and analyse the increase in students’ interest in learning after the model was implemented. The research used a Classroom Action Research (CAR) design conducted in two cycles. The research subjects were 29 fourth-grade students at MI DDI 1 Palopo. Data were collected through observation, questionnaires, and documentation, then analysed qualitatively and quantitatively. The results showed a significant increase in learning interest from cycle I to cycle II. In cycle I, the average level of learning interest reached 78% (moderate category), while in cycle II it increased to 85.25% (high category). These findings indicate that the TAI cooperative learning model can be an effective alternative to increase students’ interest in learning Fiqh.